2012
DOI: 10.3892/or.2012.1796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SEMA3G on migration and invasion of glioma cells

Abstract: Abstract. Glioblastoma multiforme is the most aggressive type of brain tumor with a strong ability to invade and migrate into surrounding normal brain tissues, leading to high tumor recurrence and mortality. Most of class-3 semaphorins, especially SEMA3A, SEMA3B and SEMA3F, have been reported to have strong tumor inhibition ability, but the role of SEMA3G in tumor biology is largely unknown. We report here that SEMA3G possesses anti-migration and anti-invasion ability. To determine the potential effects of SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
15
1
Order By: Relevance
“…Overexpression of VGF inhibits colony formation of ovarian cancer cells, however, VGF promoter hypermethylation correlates with better patient survival [72]. In contrast to our results, SEMA3G inhibits cell migration and invasion in glioma [73]. SLC5A1 promotes growth and proliferation of pancreatic cancer [74].…”
Section: Discussioncontrasting
confidence: 88%
“…Overexpression of VGF inhibits colony formation of ovarian cancer cells, however, VGF promoter hypermethylation correlates with better patient survival [72]. In contrast to our results, SEMA3G inhibits cell migration and invasion in glioma [73]. SLC5A1 promotes growth and proliferation of pancreatic cancer [74].…”
Section: Discussioncontrasting
confidence: 88%
“…SLIT/ROBO signaling, canonically involved in axon pathfinding as a chemorepulsive ligand-receptor system (Brose et al, 1999; Kidd et al, 1999), functions similarly as a chemorepellant in glioma (Mertsch et al, 2008). Semaphorins function chiefly as short-range inhibitory signals for developing axons, and HGGs express both semaphorins and the receptors plexins and neuropilins (Rieger et al, 2003); semaphorin signaling has been found to limit glioma motility (Li and Lee, 2010; Zhou et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“… 249 SEMA3G also prevents migration and invasion in an autocrine and paracrine fashion by inhibiting the activity of MMP2 in vitro, and inhibits tumor growth in an orthotopic model of GBM. 219 , 250 …”
Section: Structure Signaling and Function Of Class 3 Semaphorins Anmentioning
confidence: 99%